Estimating the incidence of interstitial lung diseases in the Cree of Eeyou Istchee, northern Québec. - Matthieu Storme; Alexandre Semionov; Deborah Assayag; Michael Lefson; Darlene Kitty; David Dannenbaum; Jill Torrie; Pierre Lejeune; Elizabeth Robinson; Faiz Ahmad Khan (PLoS ONE)
Background Little is known about the epidemiology of interstitial lung disease (ILD) amongst Canada's Indigenous populations. Clinicians working in Eeyou Istchee (the Cree territory of the James Bay region of Québec, population 17, 956) suspected that ILD was more common in this area. We sought to identify all prevalent and incident cases of ILD in Eeyou Istchee between 2006 and 2013, to describe characteristics of affected patients, distribution of subtypes, and estimate disease incidence. Methods Potential ILD cases amongst Eeyou Istchee residents were identified by searching hospitalization databases and lists of patients on long term home oxygen in the region's nine communities, and surveying physicians and nurses. Clinical, radiological and pathological data were reviewed. Potential cases were classified as 'Definite ILD' if an open lung biopsy demonstrated ILD or, in the absence of histopathologic confirmation, if their thoracic CT imaging was deemed consistent with ILD by a panel of two respirologists and a chest radiologist. Potential cases for whom CT images could not be retrieved for our review were not eligible for classification as Definite ILD, unless they had undergone open lung biopsy. The Definite ILD group was further categorized by subtype of ILD. For usual interstitial pneumonia and non-specific interstitial pneumonitis patterns, we assumed cases were idiopathic in the absence of documentation of connective tissue disease or occupational exposures in the medical chart. For Definite ILD and the most common subtype, we calculated the average annual incidence rates, age-standardized to the province of Quebec, for 2006 to 2013, using a gamma distribution to calculate 95% confidence intervals. Results Of 167 potential cases, 52 were categorized as Definite ILD: 14 on the basis of histopathology and 38 on the basis of CT imaging alone. Six patients had a prior history of connective tissue disease. Information on occupation was recorded in the charts of 18/52 (35%) cases, and missing in the remainder. We found the most common subtype was idiopathic pulmonary fibrosis (27/52, 52%), followed by idiopathic non-specific interstitial pneumonia (13/52, 25%), and secondary usual interstitial pneumonia associated with connective tissue diseases (5/52, 10%). The age-standardized annual incidence between 2006-2013 was 80 per 100,000 person-years observed (PYO) for ILD, and 46 per 100,000 PYO for idiopathic pulmonary fibrosis. Interpretation The incidence of ILD and of idiopathic pulmonary fibrosis in Eeyou Istchee may be higher than rates reported in other populations; however, cautious interpretation is required due to the lack of histopathological confirmation in the majority of cases, and our reliance on chart review to exclude secondary causes. A prospective study of incident cases with standardized assessments to establish the types of ILD and to assess for potential causes could overcome some of the limitations of the present analysis. Studies evaluating ILD incidence and subtype distribution in other Indigenous populations would also be of interest.